The impact of metal illness stigma: exploring perceptions of mental illness within Gauteng - Van Heerden, Francois (My University, 2018)
Within South Africa, growing healthcare concerns for mental illness remain, as high reported lifetime prevalence rates persist. Very little has been done in terms of measuring and gauging general perceptions of mental illnesses for the South African context. Additionally, understanding perceived differences between mental illness conditions have only been studied to a limited degree. This study explored general perceptions of mental illness of the public and evaluated knowledge, familiarity, attitudes, causal beliefs, care, and management of mental illness. It also explored attributional understandings related to emotional responses, perceived controllability, helping behaviour, and other perceptions, specifically within three vignette conditions that represented different mental illness conditions, namely: substance use disorder, schizophrenia, and depression. The questionnaire consisted of four main sections: demographic section that included general scale items related to familiarity and knowledge of mental illness, beliefs toward mental illness, public perceptions of mental illness, and the vignettes with attributional items. The questionnaire was completed by a convenience sample of 279 participants within the Gauteng region. Data was primarily analysed using descriptive statistics, correlations, mean difference comparisons, and multiple regression analyses. Knowledge was found to show stronger negative correlations with the stigma factor than familiarity. The sample showed greater preference for both psychosocial and biological aetiologies to understand mental illness. Typically, more than one care and management option was utilised while western health practices would seem to be preferred over traditional alternatives. Large significant differences were found between mental illness conditions in the vignette comparisons. In terms of the multiple regression analyses, a variety of predictors were found across care and management options with little consistency between them. However, in terms of predicting helping behaviour, fear was found to be strongest predictor across mental illness conditions. Results were discussed within the context of South Africa and within the broader understanding of mental illness and attribution theory.
A research report submitted in partial fulfillment for the degree Master of Arts in Social and Psychological Research by Coursework and Research Report (PSYC7022) in the Department of Psychology, Faculty of Humanities at the University of the Witwatersrand June 2018
Keywords: Mental illness--South Africa; Psychiatry--South Africa.